A Case Study of a Methodological Approach to Cocreating Perinatal Health Knowledge Between Western and Indigenous Communities. Issue 1 (1st March 2017) - Kandasamy, Sujane; Vanstone, Meredith; Oremus, Mark; Hill, Trista; Wahi, Gita; Wilson, Julie; Davis, A. Darlene; Jacobs, Ruby; Anglin, Rebecca; Anand, Sonia S.
This article describes the methods taken to create an understanding of the perinatal health beliefs of elder Indigenous women of the Six Nations of the Grand River in Ontario, Canada. Our study paired constructivist grounded theory data collection and analysis methods with an Indigenous epistemological framework. We aimed to create knowledge that was specific to an Indigenous context, which was useful and resonant with both Indigenous and Western readers. The multidisciplinary research team included Indigenous and non-Indigenous members and worked with a common appreciation for multiple knowledge sources. We offer an account of our process and methodological principles to serve as an illustrative case study of bringing together diverse approaches when working with Indigenous communities.